The How, Energy from Chaos, becomes The Spin of the → Discrete Elementary - Monads - Georgallides, Markos (IJRDO -JOURNAL OF MATHEMATICS, 2017)
From Mechanics in case that , in an Axisymmetric Rotating Body , with constant Angular-Velocity , w , the moment of Inertia ,